Cognitive and patient-reported outcomes in adults with pediatric-onset multiple sclerosis - Baruch, Natalie F; O'Donnell, Ellen H; Glanz, Bonnie I; Benedict, Ralph H B; Musallam, Alexander J; Healy, Brian C; Rintell, David; Chitnis, Tanuja (Multiple sclerosis, 2016)
Little is known about long-term cognitive and patient-reported outcomes of pediatric-onset multiple sclerosis (POMS). The objective of this paper is to compare cognitive and patient-reported outcomes in adults with POMS vs. adult-onset MS (AOMS). We compared standardized patient-reported measures MSQOL54, MFIS, CES-D and SDMT in adult patients with MS onset prior to and after age 18, using data gathered in the Comprehensive Longitudinal Investigations in MS at Brigham and Women's Hospital (CLIMB) study. Fifty-one POMS and 550 AOMS patients were compared. SDMT scores were significantly lower in POMS after adjusting for age (-7.57 (-11.72, -3.43; p < 0.001), but not after adjusting for disease duration. Estimated group difference demonstrated lower normative z scores in POMS vs. AOMS in unadjusted analysis (-0.74 (95% CI: -1.18, -0.30; p = 0.0009) and after adjusting for disease duration (-0.60; 95%CI: -1.05, -0.15; p = 0.0097). Findings were unchanged in a subset of POMS diagnosed prior to age 18. In unadjusted and adjusted analyses, no significant differences were observed in health-related quality-of-life, fatigue, depression or social support between POMS and AOMS. Younger age of onset was associated with more impairment in information-processing speed in adults with POMS compared to AOMS, and remained significant when controlling for disease duration in age-normed analysis. The two groups were similar in terms of patient-reported outcomes, suggesting similar qualitative experiences of MS.